2013
DOI: 10.1248/cpb.c12-00539
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Approach to Searching for Bioactive Ingredients in Cigarette Smoke

Abstract: Cigarette smoke, a collection of many toxic chemicals, contributes to the pathogenesis of smokingrelated diseases such as chronic obstructive pulmonary disease and cancer. Much work has been done on the chemical analysis of ingredients in cigarette smoke, but there are few reports on the active ingredients that can modify biomolecules. We used a sensitive liquid chromatography-mass spectrometry (LC/MS) and LC/ MS/MS method to show that l-tyrosine (Tyr), an amino acid with a highly reactive hydroxyl group, read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 12 publications
0
17
0
3
Order By: Relevance
“…5,6,13) Using GC/MS, we previously identified methyl vinyl ketone (MVK), an α,β-unsaturated ketone, as another active ingredient in cigarette smoke and demonstrated that MVK is abundantly present in cigarette smoke extract (CSE). 14) Furthermore, we clarified using LC/MS/MS and NMR that MVK could easily react with tyrosine at 37°C, a chemically reactive amino acid, to form N-(3-oxobutyl)-Tyr via Michael addition reaction. 14) We also found that GSH levels in mouse melanoma cells are rapidly reduced by exposure to CSE, and that MVK, ACR and CA irreversibly react with intracellular GSH to form the corresponding GSH adducts.…”
mentioning
confidence: 98%
“…5,6,13) Using GC/MS, we previously identified methyl vinyl ketone (MVK), an α,β-unsaturated ketone, as another active ingredient in cigarette smoke and demonstrated that MVK is abundantly present in cigarette smoke extract (CSE). 14) Furthermore, we clarified using LC/MS/MS and NMR that MVK could easily react with tyrosine at 37°C, a chemically reactive amino acid, to form N-(3-oxobutyl)-Tyr via Michael addition reaction. 14) We also found that GSH levels in mouse melanoma cells are rapidly reduced by exposure to CSE, and that MVK, ACR and CA irreversibly react with intracellular GSH to form the corresponding GSH adducts.…”
mentioning
confidence: 98%
“…Активне і пасивне куріння однаково шкідливо діє на організм, підриває здоров'я людини та загрожує її життю [1][2][3]. У димі цигарок міститься біля 1900 компонентів, під впли-вом яких можлива токсична, мутагенна та канцеро-генна дії на організм людини [4,5]. До його складу входять нікотин, аміак, піримідинові основи, діоксин, оксид вуглецю, сірководень, ціаніди, оцтова й мура-шина кислоти, поліфеноли та інші токсичні речови-ни.…”
Section: вступunclassified
“…Його важлива роль полягає у регуляції вуглеводного обміну, оскіль-ки Cr 3+ є компонентом фактора толерантності до глю-кози [4]. Американська національна академія наук (NRS) встановила, що потреба хрому для людей скла-дає від 50 до 200 мкг/добу [5].…”
Section: вступunclassified
See 1 more Smart Citation
“…[2][3][4] In particular, MVK is abundant in the gaseous phase of cigarette smoke, is present in cigarette smoke extract (CSE), and is a major mediator of cigarette smoke. [5][6][7] Cigarette smoking may increase the risk of disease development, may reduce the effectiveness of treatment, and eventually induce recurrence. 8) Cigarette smoking has a substantial influence on human health.…”
mentioning
confidence: 99%